Blood Gas Transport: Implications for O2 and CO2 Exchange in Lungs and Tissues - Wagner, Peter D. (Seminars in Respiratory and Critical Care Medicine, 2023)
The well-known ways in which O2 and CO2 (and other gases) are carried in the blood were presented in the preceding chapter. However, what the many available texts about O2 and CO2 transport do not emphasize is why knowing how gases are carried in blood matters, and this second, companion, article specifically addresses that critical aspect of gas exchange physiology. During gas exchange, both at the lungs and in the peripheral tissues, it is the shapes and the slopes of the O2 and CO2 binding curves that explain almost all of the behaviors of each gas and the quantitative differences observed between them. This conclusion is derived from first principle considerations of the gas exchange processes. Dissociation curve shape and slope differences explain most of the differences between O2 and CO2 in both diffusive exchange in the lungs and tissues and convective exchange/transport in, and between, the lungs and tissues. In fact, each of the chapters in this volume describes physiological behavior that depends more or less directly on the dissociation curves of O2 and CO2.
Keywords: inert gases; solubility; dissociation curves; diffusive gas exchange; convective gas transport; O2–CO2 interactions